Time of harvest and storability of Crotalaria juncea L. seeds (Revista Ciência Agronômica, 2023)
Although used as green manure, one of the challenges the cultivation of Crotalaria juncea is the lowavailability of quality seeds in the market. The harvest at the right time contributes to the achievement of better quality seeds.The objectives of this study were to evaluate the storability and characterize the physical and physiological changes of theseeds harvested at different times. The statistical design was completely randomized with three replications. Treatmentsconsisted of four harvest seasons and two storage periods (0 to 8 months). The samples were collected when the plantsreached 40, 60, 80 and 100% of dried pods. The following characteristics were evaluated: time for drying, moisture content,dry matter accumulation, physical purity, yield, uniformity testing, seed coat coloring, germination, germination first counttest, percentage of hard seeds, speed index and percentage of seedling emergence. Data from ripening stages were submittedto regression analysis. The effect of storage within each time it was analyzed by the joint analysis of variance of the resultsand the Tukey test (p≤0.05). The determination of the sampling point based on the percentage of dried beans is efficiently.The physiological maturity of the seeds is achieved when the plants have about 86.1% of dry beans, with the Crotalariajuncea seeds harvesting is performed at the point where the plants have between 80 and 100% of dried pods. The storage foreight months reduces dormancy up to 75.4%.